Comparison of direct anterior vs. posterior approach in primary total hip arthroplasty: a systematic review and meta-analysis on enhanced recovery after surgery - Xu, Wenqian; Lao, Jinjin; Liu, Jinsong; Zhang, Zengrui; Wan, Xiaoyu; Chen, Zhiguang; Huang, Xiaotao; Chen, Nan; Xu, Yingxing (Frontiers in Surgery, 2025)
PurposeThis meta-analysis aimed to compare the direct anterior approach (DAA) and posterior approach (PA) for total hip arthroplasty (THA) within the context of enhanced recovery after surgery (ERAS).MethodsStudies comparing DAA and PA for THA were systematically retrieved from PubMed, Embase, Web of Science, Cochrane Library, and Google Scholar databases, covering the period from 2012 to 2024. A meta-analysis was conducted to compare the ERAS-related outcomes between DAA and PA for THA using RevMan 5.3 software, including surgical trauma, muscle damage, functional recovery, and complications. Heterogeneity was considered significant if I2 > 50%, in which case a random-effects model and subgroup analysis were applied. Continuous and dichotomous data were analyzed using 95% confidence intervals (CIs). Methodological quality and heterogeneity assessments were also conducted.ResultsA total of 48 studies, including 46,367 hips (13,285 in the DAA group and 33,082 in the PA group), were included. Compared with PA, DAA was associated with significantly lower blood transfusion rates [6.62% vs. 14.52%; odds ratio (OR) = 0.73; 95% CI: 0.59–0.91; P  < 0.005], shorter hospital stay [mean difference (MD) = −0.88 days; 95% CI: −1.10 to −0.87; P < 0.001], and less gluteus minimus muscle damage on magnetic resonance imaging (MRI) (36.84% vs. 65.79%; OR = 0.28; 95% CI: 0.14–0.56; P < 0.005). Lower levels of creatine kinase (MD = −49.58; 95% CI: −56.43 to −43.26; P < 0.001) and C-reactive protein (MD = −4.48; 95% CI: −5.28 to −4.47; P < 0.001) were also observed in the DAA group. Functional outcomes, including Harris hip score (MD = 3.07; 95% CI: 0.08–6.07; P < 0.05) and short form (SF) score (MD = 1.53; 95% CI: 0.80–2.26; P < 0.001), were better with DAA. Dislocation rates were significantly lower with DAA (0.84% vs. 1.82%; OR = 0.32; 95% CI: 0.21–0.48; P < 0.001). However, there were no significant differences between DAA and PA in surgery time (MD = 2.43; 95% CI: −2.20 to 7.06; P = 0.30), gluteus medius muscle damage on MRI (17.34% vs. 15.15%; OR = 1.20; 95% CI: 0.53–2.71; P = 0.66), tensor fasciae latae muscle damage on MRI (25.51% vs. 38.38%; OR = 0.40; 95% CI: 0.03–4.97; P = 0.48), time to discontinuation of assistive devices (MD = −1.85; 95% CI: −4.05 to 0.35; P = 0.10), infection (1.09% vs. 0.60%; OR = 0.92; 95% CI: 0.48–1.77; P = 0.81), nerve injury (0.60% vs. 0.68%; OR = 1.06; 95% CI: 0.69–1.64; P = 0.79), intraoperative fracture (0.55% vs. 0.79%; OR = 0.68; 95% CI: 0.36–1.26; P = 0.22), or leg length discrepancy (MD = −1.85; 95% CI: −4.05 to 0.35; P = 0.10).ConclusionWithin the framework of ERAS, the DAA was found to be associated with reduced muscle damage, fewer postoperative complications, and improved functional recovery compared with the PA in patients undergoing THA.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/recorddashboard.